Islamic Philanthropy-Based Fintech: Design of Stock Waqf Simulation Software - Harpepen, Andi; Yustati, Herlina (Valid: Jurnal Ilmiah, 2026)
Waqf, as a form of Islamic philanthropy, has strong potential in Indonesia. Indonesia's predominantly Muslim population and the generous character of the Muslim community offer great opportunities for the development of waqf. One of the latest developments in waqf is stock waqf, which operates in the Islamic capital market as a product of Islamic philanthropy. Among university students, stock waqf literacy is still low, although the current generation is very familiar with digital technology. Therefore, the development of a stock waqf application as an educational tool can be a solution to improve students' understanding of stock waqf. The purpose of this research is to develop a stock waqf simulation application through fintech technology to improve literacy among students. The results of the development of the stock waqf simulation application have gone through various stages, including needs analysis, design, implementation, and testing. The test results show that this software fulfills the needs well, with the validity of the test reaching 100%. This indicates that the stock waqf simulation application has been successfully created and can be used to provide an understanding of stock waqf simulation.